Dissemination of a Chloramphenicol- and Tetracycline-Resistant but Penicillin-Susceptible Invasive Clone of Serotype 5 Streptococcus pneumoniae in Colombia - Tamayo, Mónica (American Society for Microbiology, 1999)
A national surveillance conducted in Colombia between 1994 and 1996 identified serotype 5 Streptococcus pneumoniae as the second most frequent cause of invasive disease in children younger than 5 years of age. All 43 serotype 5 isolates collected during this period were shown to be susceptible to penicillin, erythromycin, cefotaxime, and vancomycin, but most (38 of 43, or 88%) were highly resistant to chloramphenicol. In order to clarify a possible genetic relatedness among these isolates, additional microbiological and molecular characterizations were performed. Most (40 of 43, or 93%) of the isolates were found to be resistant to tetracycline. Pulsed-field gel electrophoresis (PFGE) patterns of chromosomal DNAs revealed that all the 43 isolates were closely related and that 38 of the 43 isolates were representatives of a “Colombian clone” of S. pneumoniae isolates which were recovered throughout the 3-year surveillance period from patients in 13 hospitals located in five Colombian cities. Isolates belonging to this Colombian clone were resistant to chloramphenicol and tetracycline, hybridized with the cat and tetM DNA probes in the same 340-kb SmaI fragment, and had identical PFGE patterns after both SmaI and ApaI digestions.